Peningkatan Hasil Belajar Siswa Kelas 9A Mata Pelajaran Fikih Materi Mawaris Melalui Penggunaan Media Pembelajaran Berbasis Aplikasi Android “Kalkulator Waris” Di Mts Al-Ma’Arif Rancalutung - Sahruli Sahruli (Concept: Journal of Social Humanities and Education, 2023)
This study aims to determine the increase in student learning outcomes after using learning media based on the android application "Heritage Calculator". Based on the results of student learning in the previous school year, it was seen that the learning outcomes were low, especially in rosette material. Therefore the authors conducted classroom action research using learning media based on the Android application "Inheritance Calculator". Mawaris learning is fiqh science material that requires accuracy and numeracy skills, so that students are able to apply each part of the heir according to predetermined rules. This study uses action research which consists of two cycles with four steps: planning, implementing, observing and reflecting. The subjects of this study were students of class 9A for the 2022/2023 school year. The research data were obtained from the results of formative tests and observation sheets. From the analysis of student learning outcomes about rose material, it was obtained an increase in learning outcomes from before, namely 62.50% in cycle 1 to 100% in cycle 2 of students who had exceeded the minimum completeness score (KKM) or increased 37.50% with an average learning outcome 73.63 in cycle 1 to 88.17 in cycle 2 or an increase of 14.53 points. The conclusion from this study is that scientific learning using learning media based on the android application "inheritance calculator" can improve student learning outcomes in the science subject in class 9A class 9A MTs Al-Ma'arif Rancalutung.